ChemInform Abstract: 3‐Arylcoumarins: Synthesis and Potent Antiinflammatory Activity. Issue 16 (April 2015) - Pu, Wenchen; Lin, Yuan; Zhang, Jianshuo; Wang, Fei; Wang, Chun; Zhang, Guolin
Abstract Thirty five 3‐arylcoumarins (III) are prepared via Perkin condensation.